CHEMICAL ANALYSIS AND CHARACTERISTICS OF VANNAME SHRIMP (Litopenaeus Vanname) CARAPACE FLOUR - Mhd Asrel Ahmad; Rahman Karnila; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Vanname shrimp is one type of shrimp that is widely consumed by the public because it has high nutritional value. This study aims to determine the proportion and proximate chemical composition of vanname shrimp carapace flour. This research method consists of two stages, namely: 1) Preparation of making vanname shrimp carapace flour, 2) Proximate analysis of vanname shrimp carapace flour. The parameters measured in the first stage are the calculation of the proportion value of the body part of the vanname shrimp and the second stage is the calculation of water, ash, protein, fat and carbohydrates content. The results of this study were the calculation of the proportion value of vanname shrimp body parts as follows: 75.10% meat, 15.23% head and 10.75% skin. Proximate chemical composition of vanname shrimp carapace flour is as follows: water content 10.46% (WW), ash content 32.32% (DW), protein content 38.38% (DW), fat content 1.95% (DW) and carbohydrates content 2.75% (by different).Keywords: vanname shrimp, proportion, carapace flour, proximate.